1997
DOI: 10.1038/sj.ijo.0800374
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic QTc interval: short-term weight loss effects

Abstract: OBJECTIVE: Prolongation of the QTc interval is a risk factor for ventricular arrhythmias and sudden death. There is a correlation between body mass index (BMI) and QTc, with longer intervals observed in obese subjects. Dieting and weight loss on selected diets are also associated with prolongation of the QTc interval, although the mechanisms and risk factors of this syndrome are not clearly established. The aim of the current investigation was to determine if short-term weight loss over seven days while living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 15 publications
2
18
1
Order By: Relevance
“…The significant increases in both systolic and diastolic pressures together with increased end systolic and diastolic volumes suggest the induction of hypertension for compansation the decreased heart work and cardiac output in MetS D r a f t 17 rats. Another compensation mechanism may be induction of QT shortening during our experiments as initial response, instead of prolonged QT observed in obese patients (Pietrobelli et al 1997). Indeed, this prolongation could be almost normalized when patients had even short-term weight loss (Bai et al 2007;Pietrobelli et al 1997) It is well accepted that MetS is a risk factor for prolonged QT, which may further increase cardiovascular morbidity and mortality in these subjects.…”
Section: R a F Tmentioning
confidence: 73%
See 1 more Smart Citation
“…The significant increases in both systolic and diastolic pressures together with increased end systolic and diastolic volumes suggest the induction of hypertension for compansation the decreased heart work and cardiac output in MetS D r a f t 17 rats. Another compensation mechanism may be induction of QT shortening during our experiments as initial response, instead of prolonged QT observed in obese patients (Pietrobelli et al 1997). Indeed, this prolongation could be almost normalized when patients had even short-term weight loss (Bai et al 2007;Pietrobelli et al 1997) It is well accepted that MetS is a risk factor for prolonged QT, which may further increase cardiovascular morbidity and mortality in these subjects.…”
Section: R a F Tmentioning
confidence: 73%
“…Another compensation mechanism may be induction of QT shortening during our experiments as initial response, instead of prolonged QT observed in obese patients (Pietrobelli et al 1997). Indeed, this prolongation could be almost normalized when patients had even short-term weight loss (Bai et al 2007;Pietrobelli et al 1997) It is well accepted that MetS is a risk factor for prolonged QT, which may further increase cardiovascular morbidity and mortality in these subjects. A short QT-interval is defined as short QT syndrome, generally a genetic disease of the electrical system of the heart and mutations in the KCNH2, KCNJ2, and KCNQ1 genes.…”
Section: R a F Tmentioning
confidence: 73%
“…An abnormal ventricular repolarization, which predisposes to sudden death upon cardiac arrhythmia [3], may contribute to the increased mortality risk since obesity has been found to be associated with a high prevalence of a prolonged QT interval in electrocardiographic (ECG) recordings [4]. Furthermore, weight loss, in particular when induced by bariatric surgery, has been found to reduce QT interval (QTc) length in many studies (for overview see Table 1) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, the validity of this observation has been challenged by one previous study [9] that demonstrated that the significance of QTc shortening upon weight loss gets lost when the QT interval is corrected for heart rate (HR) by using Fridericia or Framingham correction equation instead of the most commonly used Bazett equation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that morbid obesity is also correlated with a prolonged QTc interval 11,12) . Several studies have observed that weight loss could improve the QTc in obese subjects [12][13][14] . These results suggest that the resolution of obesity by diet or exercise can therefore help to improve the autonomic nervous system, arrhythmia, LVH, prevention of cardiac sudden death and coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%